Efeitos aleatórios no sucesso: análise crítica do modelo Talent vs Luck - Francisco Rosendo Martins de Andrade (2021)
In this work, we analyse the Talent vs Luck (TvL) model, which was proposed to investigate the roles of luck and talent in the success of individuals within a society. The authors propose a model of capital evolution (synonymous to “success”) based on lucky and unlucky events. Individuals that are subjected to unlucky events lose capital, while those that are subjected to lucky events may gain capital, depending on their talent. In this dissertation, some inadequacies of the model are pointed out, such as the fact that the authors do not analyze the effect of the number of iterations, which is a key factor in the analysis of the model. Given such problems, we have proposed an equivalent model, defined in terms of an ensemble of random walks, which allows us a more rigorous analysis of the results. Finally, we present some variations of this model.